Composition with precipitation inhibition function, application of composition and method for inhibiting hydration and dispersion of clay
By using a composition of magnesium hydroxide, aluminum hydroxide and iron hydroxide, it is closely adsorbed on the surface of the clay to inhibit hydration and dispersion, and the problem of poor effect of existing drilling fluid inhibitors in high temperature and high pressure environments is solved, and good temperature resistance and environmental protection are achieved.
Patent Information
- Application Number
- CN202411362203.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-03-28
AI Technical Summary
Existing drilling fluid inhibitors have poor inhibition effects in high temperature, high pressure and high salt-containing environments, and contain chemical components that are harmful to the environment, which has problems of insufficient environmental protection and temperature resistance.
A composition is used, which includes magnesium hydroxide, aluminum hydroxide and iron hydroxide, with a molar ratio of 2-10:0.5-1.8:1, for tight adsorption on the surface of the clay and inhibit hydration and dispersion.
This composition can effectively inhibit the hydration and dispersion of clay, have good temperature resistance and environmental protection, and reduce environmental pollution.
Smart Images

Figure CN119709140A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of drilling fluid and oilfield chemicals, and in particular to a composition with precipitation inhibition function and an application thereof and a method for inhibiting clay hydration dispersion. Background Art
[0002] In recent years, my country's oil and gas exploration has been continuously deepened and developed, and deep wells, ultra-deep wells and horizontal wells have increased day by day. More and more oil and gas fields under special environments such as high temperature, high pressure and high salt content have been discovered. Drilling fluid inhibitors are a very important chemical additive in the oil exploration and production industry. Its main function is to inhibit the expansion of the well wall and disperse the solid phase, thereby protecting the drilling pipe and other equipment during the drilling process. If the inhibitor has a weak ability to support the well wall, it will lead to problems such as well wall collapse, drill stuck, and loose cementing. In severe cases, it may even lead to wellhead collapse and accidents. Traditional drilling fluid inhibitors contain some chemical components that are unfavorable to the environment, such as heavy metals and solvents. However, inhibitors with single metal ions have the disadvantages of not being stable and strong enough in inhibition. In order to reduce the pollution of drilling operations to the environment, the industry urgently needs to develop more environmentally friendly inhibitors.
[0003] In order to improve the above problems, a composition having a precipitation inhibition function and its application and a method for inhibiting clay hydration dispersion are needed. Summary of the invention
[0004] The purpose of the present invention is to overcome the problems of poor inhibition effect, poor environmental protection and poor temperature resistance in the prior art, and to provide a composition with precipitation inhibition function and its application and a method for inhibiting clay hydration dispersion.
[0005] In order to achieve the above-mentioned object, the first aspect of the present invention provides an application of a composition with precipitation inhibition function in inhibiting clay hydration dispersion, characterized in that the composition comprises magnesium hydroxide, aluminum hydroxide and iron hydroxide; wherein the molar ratio of the magnesium hydroxide, aluminum hydroxide and iron hydroxide is 2-10:0.5-1.8:1.
[0006] The second aspect of the present invention provides a composition with precipitation inhibition function, characterized in that the composition comprises magnesium hydroxide, aluminum hydroxide and iron hydroxide; wherein the molar ratio of the magnesium hydroxide, aluminum hydroxide and iron hydroxide is 2-10:0.5-1.8:1.
[0007] The third aspect of the present invention provides a method for preparing a material for inhibiting hydration and dispersion of clay, characterized in that the method comprises:
[0008] (1) mixing a magnesium salt, an aluminum salt and an iron salt with an alkali metal hydroxide and reacting them, wherein the molar ratio of the magnesium salt, the aluminum salt and the iron salt is 2-10:0.5-1.8:1;
[0009] (2) Mixing the reaction product of step (1) with clay.
[0010] Through the above technical solution, the beneficial effects of the present invention are as follows:
[0011] 1. The composition with precipitation inhibition function provided by the present invention can be tightly adsorbed on the surface of clay, shortening the interlayer distance of bentonite, making it difficult for water molecules to enter, so it has good inhibition and temperature resistance, and has a strong inhibitory effect on clay hydration dispersion.
[0012] 2. The composition with precipitation inhibition function provided by the present invention is an inorganic multi-metal hydroxide precipitation (M-MMH), does not contain substances harmful to the environment, and has good environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 It is the crystal diagram of M-MMH and the schematic diagram of the microstructure of M-MMH.
[0014] Figure 2 1-6, Comparative Examples 1-2, M-MMH suspensions, water, and potassium chloride solutions; (b) is a linear expansion diagram of sodium bentonite in M-MMH suspensions, water, and potassium chloride solutions of Comparative Examples 3-10, respectively.
[0015] Figure 3 This is the surface condition of sodium bentonite balls after being immersed in M1-Fe suspension for 48 hours. DETAILED DESCRIPTION
[0016] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0017] As mentioned above, the first aspect of the present invention provides an application of a composition with precipitation inhibition function in inhibiting clay hydration and dispersion, characterized in that the composition comprises magnesium hydroxide, aluminum hydroxide and iron hydroxide; wherein the molar ratio of the magnesium hydroxide, aluminum hydroxide and iron hydroxide is 2-10:0.5-1.8:1 (such as 2:1.8:1, 2:1:1, 3:1:1, 4:1:1, 5:1:1, 6:1:1, 7:1:1, 8:1:1, 9:1:1, 10:1:1, 10:0.7:1 or any value between the above values).
[0018] In some embodiments of the present invention, preferably, the molar ratio of the magnesium hydroxide, aluminum hydroxide and iron hydroxide is 2.2-8:0.8-1.6:1, preferably 2.5-4:0.9-1.2:1.
[0019] The second aspect of the present invention provides a composition with precipitation inhibition function, characterized in that the composition comprises magnesium hydroxide, aluminum hydroxide and iron hydroxide; wherein the molar ratio of the magnesium hydroxide, aluminum hydroxide and iron hydroxide is 2-10:0.5-1.8:1.
[0020] In some embodiments of the present invention, preferably, the molar ratio of the magnesium hydroxide, aluminum hydroxide and iron hydroxide is 2.2-8:0.8-1.6:1, preferably 2.5-4:0.9-1.2:1.
[0021] In some embodiments of the present invention, preferably, the molar ratio of the magnesium hydroxide, aluminum hydroxide and iron hydroxide is 2-3:1:1.
[0022] According to a preferred embodiment of the present invention, the composition consists only of the above-mentioned ingredients.
[0023] In the present invention, the molar ratio of magnesium hydroxide, aluminum hydroxide and iron hydroxide in the composition can be measured by elemental analysis, or calculated by the ratio of the feeding amounts of the following magnesium salt, aluminum salt and iron salt.
[0024] A third aspect of the present invention provides a method for inhibiting hydration and dispersion of clay, characterized in that the method comprises:
[0025] (1) mixing a magnesium salt, an aluminum salt and an iron salt with an alkali metal hydroxide and reacting them, wherein the molar ratio of the magnesium salt, the aluminum salt and the iron salt is 2-10:0.5-1.8:1;
[0026] (2) Mixing the reaction product of step (1) with clay.
[0027] In some embodiments of the present invention, preferably, the magnesium salt, aluminum salt and iron salt are each independently selected from monobasic acid salts having a solubility greater than 65 g / 100 g water at 20°C.
[0028] In some embodiments of the present invention, preferably, the molar ratio of the magnesium salt, the aluminum salt and the iron salt is 2-10:0.5-1.8:1 (such as 2:1.8:1, 2:1:1, 3:1:1, 4:1:1, 5:1:1, 6:1:1, 7:1:1, 8:1:1, 9:1:1, 10:1:1, 10:0.7:1 or any value between the above values).
[0029] In some embodiments of the present invention, preferably, the monoacid is selected from inorganic acids, preferably at least one of hydrochloric acid, hydrobromic acid and nitric acid.
[0030] In some embodiments of the present invention, preferably, the alkali metal hydroxide is selected from sodium hydroxide and / or potassium hydroxide.
[0031] In some embodiments of the present invention, preferably, the molar ratio of the magnesium salt, the aluminum salt and the iron salt is 2.2-8:0.8-1.6:1, preferably 2.5-4:0.9-1.2:1.
[0032] In some embodiments of the present invention, preferably, the molar ratio of the magnesium salt, the aluminum salt and the iron salt is 2-3:1:1.
[0033] In some embodiments of the present invention, preferably, the molar ratio of the sum of the magnesium salt, the aluminum salt and the iron salt to the alkali metal hydroxide is 1:2-3, preferably 1:2.18-2.55, and more preferably 1:2.32-2.47.
[0034] In some embodiments of the present invention, preferably, the reaction temperature is 40-50°C, preferably 45-50°C.
[0035] In some embodiments of the present invention, preferably, the reaction time is 180-240 min, preferably 180-210 min.
[0036] In some embodiments of the present invention, preferably, the mixing conditions include: temperature of 30-150° C., pressure of 1-15 MPa, and time of 5-60 min.
[0037] In some embodiments of the present invention, preferably, the amount of the reaction product of step (1) is 10-40 g per kilogram of clay on a dry basis.
[0038] In some embodiments of the present invention, preferably, the clay is selected from at least one of kaolin, bentonite and activated clay, preferably bentonite, and more preferably at least one of sodium bentonite, calcium bentonite, hydrogen bentonite and organic bentonite. . . .
[0039] The present invention will be described in detail below through examples. In the following examples, the linear expansion coefficient is measured by the water-based drilling fluid field test procedure standard SY / T 16783-1997 method; the magnesium hydroxide raw material is an industrial grade commercial product of Tianjin Shengao Chemical Reagent Co., Ltd.; the aluminum hydroxide raw material is an industrial grade commercial product of Tianjin Shengao Chemical Reagent Co., Ltd.; the iron hydroxide raw material is an industrial grade commercial product of Tianjin Shengao Chemical Reagent Co., Ltd.; and the sodium bentonite is an industrial grade commercial product of Xi'an Fengyun Chemical Co., Ltd.
[0040] Example 1
[0041] 2.5 mol of magnesium chloride, aluminum chloride, and ferric chloride were mixed with 500 g of water to obtain an aqueous solution, and 60 L of 0.1 mol / L sodium hydroxide solution was added dropwise (the dropping speed was 2 L / h) to the reaction solution, and the mixture was stirred at 50° C. for 180 min at a stirring rate of 600 r / min. The molar ratio of magnesium chloride, aluminum chloride, ferric chloride, and sodium hydroxide was 3:1:1:12;
[0042] After the reaction, the reaction solution was centrifuged at a speed of 2000 r / min for 15 minutes. The centrifuged sample I was washed with distilled water, and the centrifugation-washing step 6 was repeated. The centrifuged sample I was washed with distilled water and dried in turn at a drying temperature of 105°C and a drying time of 24 hours to obtain sample II. After grinding, sample II was passed through a 100-mesh sieve to obtain a composition (M-MMH), recorded as M1-Fe.
[0043] Example 2
[0044] The method described in Example 1 was followed, except that 0.1 mol / L potassium hydroxide solution was used instead of 0.1 mol / L sodium hydroxide solution to obtain M-MMH, which was recorded as M2-Fe.
[0045] Example 3
[0046] The method described in Example 1 was followed, except that the nitrates of magnesium, aluminum and iron were used instead of their respective hydrochlorides, and the resulting M-MMH was recorded as M3-Fe.
[0047] Example 4
[0048] Magnesium hydroxide, aluminum hydroxide and iron hydroxide were mixed in a molar ratio of 2.5:1:1 to obtain M-MMH, which was recorded as M4-Fe.
[0049] Example 5
[0050] Magnesium hydroxide, aluminum hydroxide and iron hydroxide are mixed in a molar ratio of 2:1:1 to obtain M-MMH, which is recorded as M5-Fe.
[0051] Example 6
[0052] Magnesium hydroxide, aluminum hydroxide and iron hydroxide were mixed in a molar ratio of 3:1:1 to obtain M-MMH, which was recorded as M6-Fe.
[0053] Comparative Example 1
[0054] The method described in Example 1 was followed, except that the molar ratio of magnesium chloride, aluminum chloride, ferric chloride and sodium hydroxide was 3:2:2:18, and the obtained M-MMH was recorded as M7-Fe.
[0055] Comparative Example 2
[0056] The method described in Example 1 was followed, except that the molar ratio of magnesium chloride, aluminum chloride, ferric chloride and sodium hydroxide was 2:3:3:24, and the obtained M-MMH was recorded as M8-Fe.
[0057] Comparative Example 3
[0058] The method described in Example 1 was followed, except that the molar ratio of magnesium chloride, aluminum chloride, ferric chloride and sodium hydroxide was 3:1:3:18, and the obtained M-MMH was recorded as M9-Fe.
[0059] Comparative Example 4
[0060] The method described in Example 1 was followed, except that the molar ratio of magnesium chloride, aluminum chloride, ferric chloride and sodium hydroxide was 3:2:1:15, and the obtained M-MMH was recorded as M10-Fe.
[0061] Comparative Example 5
[0062] The method described in Example 1 was followed, except that the molar ratio of magnesium chloride, aluminum chloride, ferric chloride and sodium hydroxide was 3:2:3:21, and the obtained M-MMH was recorded as M11-Fe.
[0063] Comparative Example 6
[0064] The method described in Example 1 was followed, except that the molar ratio of magnesium chloride, aluminum chloride, ferric chloride and sodium hydroxide was 2:1:2:16, and the obtained M-MMH was recorded as M12-Fe.
[0065] Comparative Example 7
[0066] The method described in Example 1 was followed, except that the molar ratio of magnesium chloride, aluminum chloride, ferric chloride and sodium hydroxide was 3:1:2:15, and the obtained M-MMH was recorded as M13-Fe.
[0067] Comparative Example 8
[0068] The method of Example 1 is followed, except that zinc chloride is used instead of magnesium chloride, and the obtained high temperature resistant and environmentally friendly multi-metal hydroxide precipitation inhibitor is recorded as M14-Zn.
[0069] Comparative Example 9
[0070] The method of Example 1 is followed, except that copper chloride is used instead of aluminum chloride to obtain a high temperature resistant and environment-friendly multi-metal hydroxide precipitation inhibitor, which is denoted as M15-Cu.
[0071] Comparative Example 10
[0072] The method of Example 1 is followed, except that copper chloride is used instead of ferric chloride to obtain a high temperature resistant and environment-friendly multi-metal hydroxide precipitation inhibitor, which is denoted as M16-Cu.
[0073] Comparative Example 11
[0074] The method of Example 1 was followed, except that magnesium chloride was not added, and the obtained high temperature resistant and environmentally friendly binary metal hydroxide precipitation inhibitor was recorded as M17-FeAl.
[0075] Comparative Example 12
[0076] The method of Example 1 was followed, except that aluminum chloride was not added, and the obtained high temperature resistant and environmentally friendly binary metal hydroxide precipitation inhibitor was recorded as M18-FeMg.
[0077] Comparative Example 13
[0078] The method of Example 1 was followed, except that ferric chloride was not added, and the obtained high temperature resistant and environmentally friendly binary metal hydroxide precipitation inhibitor was recorded as M19-MgAl.
[0079] Comparative Example 14
[0080] The method of Example 1 was followed, except that magnesium chloride and aluminum chloride were not added, and the obtained high temperature resistant and environmentally friendly monometallic hydroxide precipitation inhibitor was denoted as M20-Fe.
[0081] Comparative Example 15
[0082] The method of Example 1 was followed, except that magnesium chloride and ferric chloride were not added, and the obtained high temperature resistant and environment-friendly monometallic hydroxide precipitation inhibitor was denoted as M21-Al.
[0083] Comparative Example 16
[0084] The method of Example 1 was followed, except that aluminum chloride and ferric chloride were not added, and the obtained high temperature resistant and environment-friendly monometallic hydroxide precipitation inhibitor was recorded as M22-Mg.
[0085] Test Case
[0086] The metal hydroxide precipitation inhibitors prepared in the above examples and comparative examples were respectively prepared into suspensions with a mass fraction of 4% (other components were water), and the performance was evaluated with a mass fraction of 4% potassium chloride solution and water by the following experimental methods:
[0087] 1. High temperature linear expansion test
[0088] According to the standard SY / T 16783-1997 for field testing procedures of water-based drilling fluids, 10.05 g of sodium bentonite dried at 105°C for 4 hours was taken, and the sodium bentonite was loaded into a core making instrument according to the test standard. The core making instrument was pressed at a pressure of 10 MPa for 10 minutes using a press to make a core pressed sheet. The prepared suspensions of 4 wt% M1-Fe, M5-Fe to M13-Fe, M14-Zn, M15-Cu, and M16-Cu (other components are water), water, and potassium chloride solution were poured into the linear expansion instrument respectively, and confirmed to be at 90°C. When the suspension, water, and potassium chloride solution reached the scale of the linear expansion instrument, a stopwatch was used to time the time, and the linear expansion instrument readings were recorded according to the experimental standard. The results are as follows: Figure 2 As shown. Figure 2 (a) and Figure 2 (b) It can be seen that the expansion rate of the sodium bentonite added with the multi-metal hydroxide precipitation inhibitor prepared in Examples 1-4 is significantly smaller than that of the comparative example, clean water and potassium chloride solution, which shows that the M-MMH prepared by the technical solution of the present invention also has the beneficial effect of inhibiting hydration dispersion at high temperature and has strong temperature resistance.
[0089] 2. Anti-swelling test
[0090] Sodium bentonite was dried at 105°C for 4 hours, 0.5 g of sodium bentonite was taken and put into a centrifuge tube, and 10 mL of 4 wt% of the metal hydroxide precipitation inhibitor suspension (other component was water) of each embodiment and comparative example was added into the tube, and the tube was shaken for 1 minute and allowed to stand for 2 hours, and then centrifuged at 1500 r / min for 15 minutes, and the scale of the linear expansion instrument was read. The results are shown in Table 1.
[0091] Table 1
[0092] name Anti-swelling rate / % M1-Fe 83.13 M2-Fe 82.12 M3-Fe 82.56 M4-Fe 81.14 M5-Fe 80.17 M6-Fe 81.23 M7-Fe 71.13 M8-Fe 72.15 M9-Fe 72.15 M10-Fe 66.12 M11-Fe 64.15 M12-Fe 59.25 M13-Fe 66.16 M14-Zn 58.12 M15-Cu 66.15 M16-Cu 57.45 M17-FeAl 46.15 M18-FeMg 44.23 M19-MgAl 40.13 M20-Fe 43.56 M21-Al 41.75 M22-Mg 33.12
[0093] 3. Mud ball test
[0094] Take sodium bentonite dried at 105°C for 4 hours, mix it evenly into a 10g mud ball according to the mass ratio of sodium bentonite: water = 1:1, then add the prepared 4% M1-Fe sample suspension (the other component is water) to the mud ball, use clean water as the control group, soak for 24 hours, take pictures at 48 hours, observe the overall situation of the mud ball, and evaluate the inhibition of M-MMH by the surface state and overall morphology changes of the mud ball at different stages. The results are as follows Figure 3 As shown. Figure 3 It can be seen that the control group using only clean water mixed with the sodium bentonite showed hydration and dispersion after 24 hours and 48 hours, while the mud ball added with M-MMH prepared in Example 1 of the present invention can ensure a relatively complete shape whether after 24 hours or 48 hours, which shows that the M-MMH prepared by the technical solution of the present invention has a beneficial effect of inhibiting hydration and dispersion. The compositions of the M-MMH prepared in Examples 1-6 are similar, and the only difference is that the raw materials or reagents used in the preparation method are different, or the molar ratio of magnesium hydroxide, aluminum hydroxide and iron hydroxide therein is slightly different, so the hydration and dispersion inhibition effects of these six M-MMHs are very similar.
[0095] It can be seen from the results in Table 1 that the embodiments using the technical solution of the present invention have beneficial effects such as good inhibition of clay hydration and dispersion and good temperature resistance compared with the comparative examples.
[0096] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. Use of the composition in inhibiting hydration and dispersion of clay, characterized in that: The composition includes magnesium hydroxide, aluminum hydroxide and iron hydroxide; Wherein, the molar ratio of the magnesium hydroxide, aluminum hydroxide and iron hydroxide is 2-10:0.5-1.8:
1.
2. The use according to claim 1, wherein: The molar ratio of the magnesium hydroxide, aluminum hydroxide and iron hydroxide is 2.2-8:0.8-1.6:1, preferably 2.5-4:0.9-1.2:
1.
3. A composition having a precipitation inhibition function, characterized in that: The composition includes magnesium hydroxide, aluminum hydroxide and iron hydroxide; Wherein, the molar ratio of the magnesium hydroxide, aluminum hydroxide and iron hydroxide is 2-10:0.5-1.8:
1.
4. The composition according to claim 3, wherein The molar ratio of the magnesium hydroxide, aluminum hydroxide and iron hydroxide is 2.2-8:0.8-1.6:1, preferably 2.5-4:0.9-1.2:
1.
5. A method for inhibiting hydration and dispersion of clay, characterized in that: The method includes: (1) mixing a magnesium salt, an aluminum salt and an iron salt with an alkali metal hydroxide and reacting them, wherein the molar ratio of the magnesium salt, the aluminum salt and the iron salt is 2-10:0.5-1.8:1; (2) Mixing the reaction product of step (1) with clay.
6. The method according to claim 5, wherein: The magnesium salt, aluminum salt and iron salt are each independently selected from monobasic acid salts having a solubility greater than 65 g / 100 g water at 20° C.; Preferably, the monoacid is selected from inorganic acids, preferably at least one of hydrochloric acid, hydrobromic acid and nitric acid; Preferably, the alkali metal hydroxide is selected from sodium hydroxide and / or potassium hydroxide.
7. The method according to claim 5 or 6, wherein: The molar ratio of the magnesium salt, the aluminum salt and the iron salt is 2.2-8:0.8-1.6:1, preferably 2.5-4:0.9-1.2:
1.
8. The method according to any one of claims 5 to 7, wherein: The molar ratio of the sum of the magnesium salt, the aluminum salt and the iron salt to the alkali metal hydroxide is 1:2-3, preferably 1:2.18-2.55, and more preferably 1:2.32-2.
47.
9. The method according to any one of claims 5 to 8, wherein: The reaction temperature is 40-50°C, preferably 45-50°C; And / or, the reaction time is 180-240 min, preferably 180-210 min.
10. The method according to any one of claims 5 to 9, wherein: The mixing conditions include: temperature of 30-150° C., pressure of 1-15 MPa, and time of 5-60 min.
11. The method according to any one of claims 5 to 10, wherein: The amount of the reaction product of step (1) used is 10-40 g per kilogram of clay on a dry basis.
12. The method according to any one of claims 5 to 11, wherein: The clay is selected from at least one of kaolin, bentonite and activated clay, preferably bentonite, and more preferably at least one of sodium bentonite, calcium bentonite, hydrogen bentonite and organic bentonite.